2007
DOI: 10.1529/biophysj.106.093914
|View full text |Cite
|
Sign up to set email alerts
|

A Stiffness Switch in Human Immunodeficiency Virus

Abstract: After budding from the cell, human immunodeficiency virus (HIV) and other retrovirus particles undergo a maturation process that is required for their infectivity. During maturation, HIV particles undergo a significant internal morphological reorganization, changing from a roughly spherically symmetric immature particle with a thick protein shell to a mature particle with a thin protein shell and conical core. However, the physical principles underlying viral particle production, maturation, and entry into cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
249
2
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(264 citation statements)
references
References 31 publications
5
249
2
8
Order By: Relevance
“…A recent single-molecule experiment [31][32][33][34] demonstrated that the regulation of mechanical properties in some biological processes has a significant biological importance. For example, for enhancing their infectivity, the human immunodeficiency virus (HIV) and other retrovirus particles undergo a maturation process, during which they experience a significant internal morphological reorganization, changing from roughly spherically symmetric immature particles with a thick protein shell to mature particles with a thin protein shell and conical core.…”
Section: Discussionmentioning
confidence: 99%
“…A recent single-molecule experiment [31][32][33][34] demonstrated that the regulation of mechanical properties in some biological processes has a significant biological importance. For example, for enhancing their infectivity, the human immunodeficiency virus (HIV) and other retrovirus particles undergo a maturation process, during which they experience a significant internal morphological reorganization, changing from roughly spherically symmetric immature particles with a thick protein shell to mature particles with a thin protein shell and conical core.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses are able to dynamically modulate their mechanical properties in response to external forces, so as to withstand those forces or to ease cell infection 4 . For instance, in the human immunodeficiency and murine leukemia viruses, the stiffness largely decreases during the maturation process, acting as a mechanical switch for the infection process 5 . Strikingly, a single point mutation in the capsid protein of some viruses can significantly change their elasticity 6 .…”
mentioning
confidence: 99%
“…Very recently, the same authors [53] have used this technique to measure the mechanical properties of the human immunoinsufficiency virus (HIV), likewise as a function of maturity. The immature particles were found to be 14-fold stiffer than mature ones.…”
Section: Virusesmentioning
confidence: 99%